2022
DOI: 10.3389/fimmu.2022.1065739
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum urate and telomere length and inflammation markers: Evidence from UK Biobank cohort

Abstract: ObjectiveHyperuricemia and gout have become gradually more common. The effect of serum urate on organism aging and systematic inflammation is not determined. This study aims to evaluate whether serum urate is causally associated with cellular aging markers and serum inflammation markers.MethodsA Mendelian randomization study was performed on summary-level data from the largest published genome-wide association studies. Single nucleotide polymorphisms with a genome-wide significance level were selected as instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
2
3
0
Order By: Relevance
“…Urate levels, also retained as a relevant predictor of LTL by the Lasso regression analysis, displayed a negative association with LTL ( ). As previously reported [ 31 ], MR analyses showed that elevated urate levels decreased LTL ( ), possibly due to increased cellular stress and reactive oxygen species production [ 32 ] (Fig. 2 f).…”
Section: Resultssupporting
confidence: 80%
“…Urate levels, also retained as a relevant predictor of LTL by the Lasso regression analysis, displayed a negative association with LTL ( ). As previously reported [ 31 ], MR analyses showed that elevated urate levels decreased LTL ( ), possibly due to increased cellular stress and reactive oxygen species production [ 32 ] (Fig. 2 f).…”
Section: Resultssupporting
confidence: 80%
“…Lasso analysis retained both urate (β = −0.025; p = 2.1e−44) and cystatin C (β = −0.033; p = 2.2e−75) levels as relevant predictors of LTL (Table 1), highlighting the link between kidney function and LTL. As previously reported [45], MR analyses showed that elevated urate levels decreased LTL (αT →LT L = −0.042; p = 9.4e−18), possibly due to increased cellular stress and reactive oxygen species production [46]. The urate-LTL association was significantly mediated by CRP, confirming the role of inflammation in this process (P M = 34.7%; 95%-CI[17.1%; 55.6%]).…”
Section: Renal Healthsupporting
confidence: 80%
“…A cohort study (Wei et al, 2021) from China also found a relationship between prematernal overweight and shorter neonatal telomeres. The specific mechanisms still require elucidation but could involve pathways influencing metabolism, growth factors, and inflammation (Movérare-Skrtic et al, 2009;Xu et al, 2014;Lv et al, 2022). Mendelian randomization analyses to investigate associations between birth weight and telomere length.…”
Section: Discussion Mechanismmentioning
confidence: 99%